2016
DOI: 10.1159/000448864
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Management of Hepatocellular Carcinoma with Special Emphasis on Treatment with Regorafenib and Immune Checkpoint Inhibitors

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer and the third leading cause of cancer deaths worldwide. Sonazoid-enhanced ultrasound and gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid-enhanced MRI are the most important imaging modalities in diagnosing HCC. There are 2 non-contradictory HCC treatment algorithms in Japan. Hepatic arterial infusion chemotherapy plays an important role in the treatment of advanced HCC with main or branch portal vein invasion. Regorafenib, as a second-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Recently, it was also reported that PD-1 expression promotes tumor growth, where PD-1 binds the downstream effectors of mammalian target of rapamycin (mTOR) and promotes their phosphorylation; the combination of mTOR inhibition with anti-PD-1 antibody results in a synergic tumor regression [32] . Based on these findings, clinical trials of immunomodulation of tumor microenvironment through intervention of oncogenic signaling are ongoing [33][34][35][36][37][38][39] . These trials include immune checkpoint inhibition combined with tyrosine kinase inhibitors [40,41] and other types of immune checkpoint inhibitors such as CTLA-4 antibody as well as immune checkpoint therapy combined with locoregional therapy such as resection [42][43][44] , ablation [45,46] , transarterial chemoembolization [47,48] , and hepatic arterial infusion chemotherapy [49,50] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was also reported that PD-1 expression promotes tumor growth, where PD-1 binds the downstream effectors of mammalian target of rapamycin (mTOR) and promotes their phosphorylation; the combination of mTOR inhibition with anti-PD-1 antibody results in a synergic tumor regression [32] . Based on these findings, clinical trials of immunomodulation of tumor microenvironment through intervention of oncogenic signaling are ongoing [33][34][35][36][37][38][39] . These trials include immune checkpoint inhibition combined with tyrosine kinase inhibitors [40,41] and other types of immune checkpoint inhibitors such as CTLA-4 antibody as well as immune checkpoint therapy combined with locoregional therapy such as resection [42][43][44] , ablation [45,46] , transarterial chemoembolization [47,48] , and hepatic arterial infusion chemotherapy [49,50] .…”
Section: Resultsmentioning
confidence: 99%
“…Patients with a Child-Pugh score of 5-7 and meeting the up-to-7 criteria were classified as substage B1, those with a Child-Pugh score of 5-7 and exceeding the up-to-7 criteria were classified as substage B2, and those with a Child-Pugh score of 8-9 and any up-to-7 criteria status were classified as substage B3 [16,24] .…”
Section: Modified Bolondi Classification (Kinki Criteria)mentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of aggressive tumors that usually arise on top of background of liver cirrhosis (1). It is the fifth most common cancer in the world (2). Also, it is the third most common cause of cancer related deaths (1).…”
Section: Introductionmentioning
confidence: 99%